Comparative pharmacokinetics study of anastrozole after single administration and combination with celecoxib. (4th March 2018) - Sun, Xiaoyang; Lv, Mingming; Wang, Binjie; Zhao, Simin; Guo, Ping; Wang, Shixiao; Gu, Liqiang; Chen, Xiaohui
Abstract: 1. There are numerous investigations demonstrating that the cyclooxygenase-2 (COX-2) inhibitors might enhance the efficiency of anastrozole in breast cancer. Hence, this study was conducted to investigate the comparative pharmacokinetics of anastrozole after single administration and combination with celecoxib. 2. A simple protein precipitation procedure was adopted for the sample preparation with satisfactory extraction recovery for both anastrozole and the internal standard, and then anastrozole was separated and analysed on an ACQUITY BEH UPLC C18 column (50 × 2.0 mm, 1.7 μm, Waters) within 2 min. The calibration curves showed good linarites ( r  =   0.994). Intra- and inter-day precision were within 4.93 and 13.83%, respectively. The mean extraction recoveries across QC levels were within 91.4%, and the matrix effects were within 94.5%. 3. Results showed that the method was reliable to determine anastrozole in rat plasma. Compared with rats in single administration group, no significant difference was found in the combination group. It is workable to use celecoxib combined with anastrozole in clinical therapy.